Near-infrared mediated polymer-coated carbon nanodots loaded cisplatin for targeted care management of lung cancer therapy. (December 2020) - Fang, Wei; Jin, Ronghui; Mu, Wei
Graphical abstract: Highlights: We have effectively synthesized the PEGlyated carbon nanodots loaded cisplatin was fabricated and characterised. It shows excellent in vitro cytotoxicity against lung cancer cells and non-cancerous cell. Further, examined the morphological changes in biochemical staining methods. The apoptosis mechanism was confirmed by flow cytometry analysis and was quantified. Abstract: The Cisplatin and its analogues are scarce for the second leading human health problem, cancer. Therefore, we have effectively engineered the PEGlyated carbon nanodots loaded with cisplatin PEG-CDs@Cis-Pt(IV) for targeted lung cancer therapy. The PEG-CDs@Cis-Pt(IV) confirmed by the electroscopic and spectroscopic methods. The in vitro cytotoxicity of the nanoparticles evaluated two lung cancers (A549 and HEL-299), and one non-cancerous cell line (HUVECs) were used in this study by using MTT assay. The nanoparticles are effectively killing cancer cells without affecting the nano-cancerous cells. Further, dual AO-EB fluorescent staining assay established the programmed cell death through cell morphological changes. Further, flow cytometry confirmed the induction of apoptosis by S phase arrest of the cancer cell cycle by the complexes. The results of our investigations also bear witness to CDs@Cis-Pt(IV)+NIR-NPs promising scope and potency care management for precise cancer therapy beyond platinum drugs.